Examining Japan's lost decades - Funabashi, Yoichi; Kushner, Barak (Routledge, 2015)
This volume brings together leading scholars to analyze Japan's "lost decades" after the burst of the asset bubble. It examines the economic, political, and social factors behind prolonged stagnation and considers the lessons and implications for Japan's future and other advanced economies.